Evaluation of the Timeliness of Outpatient Medical Record Document Provision Based on Minimum Service Standards - Loura Weryco Latupeirissa; Dede Setiawan; Tuti Herawati; Husni Hidayat Malik; Riantina Luxiarti (Awatara Publisher, 2026)
Timely provision of outpatient medical record documents is an essential indicator of hospital service quality because it supports continuity of care, reduces patient waiting time, and improves operational efficiency. Delays in document retrieval may disrupt clinical workflows and affect the overall quality of healthcare services. This study aimed to evaluate the timeliness of outpatient medical record document provision at Hospital X, Cirebon Regency, Indonesia, based on the Indonesian Minimum Service Standards (MSS). A quantitative descriptive research design was employed. The study was conducted in May 2026 using direct observation of 100 outpatient medical record documents selected through consecutive sampling from a population of 11,626 outpatient visits. Data were collected using a structured observation checklist and analyzed descriptively by calculating frequencies, percentages, and measures of central tendency. The findings revealed that only 33.0% of outpatient medical record documents were provided within the required standard of ≤10 minutes, while 67.0% exceeded the standard. The mean document provision time was 10.53 minutes, with a minimum time of 2 minutes and a maximum of 22 minutes. These findings indicate that the outpatient medical record service at Hospital X has not yet fully complied with the Indonesian Minimum Service Standards. Strengthening filing management, optimizing document retrieval procedures, enhancing staff competency, and implementing continuous performance monitoring are recommended to improve the timeliness of medical record document provision and the overall quality of outpatient healthcare services.